Associations between residual feed intake and apparent nutrient digestibility, in vitro methane-producing activity, and volatile fatty acid concentrations in growing beef cattle1. (7th June 2019) - Johnson, Jocelyn R; Carstens, Gordon E; Krueger, Wimberly K; Lancaster, Phillip A; Brown, Erin G; Tedeschi, Luis O; Anderson, Robin C; Johnson, Kristen A; Brosh, Arieh
Abstract: The objectives of this study were to examine the relationship between residual feed intake (RFI ) and DM and nutrient digestibility, in vitro methane production, and volatile fatty acid (VFA ) concentrations in growing beef cattle. Residual feed intake was measured in growing Santa Gertrudis steers (Study 1; n = 57; initial BW = 291.1 ± 33.8 kg) and Brangus heifers (Study 2; n = 468; initial BW = 271.4 ± 26.1 kg) fed a high-roughage-based diet (ME = 2.1 Mcal/kg DM) for 70 d in a Calan-gate feeding barn. Animals were ranked by RFI based on performance and feed intake measured from day 0 to 70 (Study 1) or day 56 (Study 2) of the trial, and 20 animals with the lowest and highest RFI were identified for subsequent collections of fecal and feed refusal samples for DM and nutrient digestibility analysis. In Study 2, rumen fluid and feces were collected for in vitro methane-producing activity (MPA ) and VFA analysis in trials 2, 3, and 4. Residual feed intake classification did not affect BW or BW gain ( P > 0.05), but low-RFI steers and heifers both consumed 19% less ( P < 0.01) DMI compared with high-RFI animals. Steers with low RFI tended ( P < 0.1) to have higher DM digestibility (DMD ) compared with high-RFI steers (70.3 vs. 66.5 ± 1.6% DM). Heifers with low RFI had 4% higher DMD (76.3 vs. 73.3 ± 1.0% DM) and 4 to 5% higher ( P < 0.01) CP, NDF, and ADF digestibility compared with heifers with high RFI. Low-RFI heifers emitted 14% less ( P < 0.01) methane (% GE intake; GEI) calculated according to Blaxter and Clapperton (1965) as modified by Wilkerson et al. (1995), and tended ( P = 0.09) to have a higher rumen acetate:propionate ratio than heifers with high RFI (GEI = 5.58 vs. 6.51 ± 0.08%; A:P ratio = 5.02 vs. 4.82 ± 0.14%). Stepwise regression analysis revealed that apparent nutrient digestibilities (DMD and NDF digestibility) for Study 1 and Study 2 accounted for an additional 8 and 6%, respectively, of the variation in intake unaccounted for by ADG and mid-test BW 0.75 . When DMD, NDF digestibility, and total ruminal VFA were added to the base model for Study 2, trials 2, 3, and 4, the R 2 increased from 0.33 to 0.47, explaining an additional 15% of the variation in DMI unrelated to growth and body size. On the basis of the results of these studies, differences in observed phenotypic RFI in growing beef animals may be a result of inter-animal variation in apparent nutrient digestibility and ruminal VFA concentrations.